The Role of Islam in the Management and Administration of Brunei Darussalam - Fatin Rabia'tul Adawiyah Md Fareed (Islamic Research, 2020)
Islam plays an essential role in forming and shaping an Islamic country. Similarly, Brunei Darussalam, an Islamic country, has made every effort to inculcate Islamic values ​​in various aspects of the country's management and administration. This concept paper aims to provide exposure regarding the role of Islam in the management and administration of Brunei Darussalam by describing the history of the arrival of Islam in Brunei Darussalam and the role of Islam in the management and administration of the country. This concept paper uses a qualitative method in the form of a library concerning secondary sources only. The results of the study found that the leadership of the Sultan is a major factor that contributes to the strong application of Islamic teachings in the management and administration of the country, and among the five main aspects that receive the influence of Islamic teachings are aspects of government and administration, administration of Islamic law, religious institutions, Islamic education, and economy. The effect of the application of Islamic teachings has strengthened the country's identity to become an Islamic state.